2018
DOI: 10.17521/cjpe.2017.0214
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes of vegetation water use efficiency and its influencing factors in Northern China

Abstract: Aims Water use efficiency (WUE) is an important variable for evaluating the growth adaptation of vegetation; it links carbon and water cycles of terrestrial ecosystems. Charactering the spatial and temporal variations in WUE and the driving factors not only can help understand the processes and regulations of ecosystem carbon and water cycles, but also provides scientific basis for formulating sustainable regional development policies and guiding water resources management. This study was conducted to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
2
0
0
Order By: Relevance
“…The average WUE values of the different vegetation types ranked in the order of forest, cropland, grassland, wetland, shrubland, and bareland, respectively, were in general agreement with the results of previous studies (Feng et al, 2018;Chang et al, 2021). Although the WUE values followed the same order rule, the same land-use type showed different WUE values in different regions, which is consistent with the conclusions of other researchers (Liu et al, 2015;Muhammad et al, 2018).…”
Section: B a Figure 10supporting
confidence: 91%
“…The average WUE values of the different vegetation types ranked in the order of forest, cropland, grassland, wetland, shrubland, and bareland, respectively, were in general agreement with the results of previous studies (Feng et al, 2018;Chang et al, 2021). Although the WUE values followed the same order rule, the same land-use type showed different WUE values in different regions, which is consistent with the conclusions of other researchers (Liu et al, 2015;Muhammad et al, 2018).…”
Section: B a Figure 10supporting
confidence: 91%
“…Our study showed that VPD was the main factor affecting the WUE s of leaves in a larch forest at different canopy heights, which was similar to the results of Zhou et al [56] and Feng et al [57]. This can be explained by the fact that the fewer short-term changes in LAI, the relative stability of the ratio of transpiration (Tr) to ET [46] and changes in VPD directly affect changes in Gs that in turn affect WUE s [23].…”
Section: Effect Of Meteorological Factors On Wue S Of Larch Forest At...supporting
confidence: 90%